MORPHOLOGICAL AND ANATOMICAL ADAPTATIONS OF THE TUBER FOR PARASITISM IN THREE SPECIES OF Balanophora J.R. Forst. et G. Forst. FROM MU CANG CHAI, YEN BAI - Hoang Tuan, Cao; Van Dung, Luong; Dao Cam Tu, Nguyen; Thuy Linh, Tran; Vu Kim Anh, Tran; Thu Ha, Bui (HNUE Journal of Science: Journal of Natural Sciences, 2025)
The genus Balanophora J.R. Forst. et G. Forst. (Balanophoraceae) includes obligate holoparasitic plants that lack chlorophyll and are completely dependent on their hosts for water and nutrients. This study investigates the morphological and anatomical characteristics of the tuber in three Balanophora species (B. fungosa, B. laxiflora, and B. harlandii) collected from Mu Cang Chai, Yen Bai, Vietnam. Detailed observations were conducted to describe the structural adaptations related to parasitism, focusing on the organization of the tuber and the development of composite bundles that form the host–parasite interface. The results reveal that the tuber functions as a highly specialized parasitic organ, consisting of an outer cortex, matrix parenchyma, parasite vascular bundles, and composite bundles. The composite bundles play a pivotal role in resource exchange between the host and the parasite, with transfer cells facilitating efficient nutrient absorption. These findings provide new insights into the structural and functional adaptations of Balanophora, contributing to a better understanding of the evolutionary strategies of holoparasitic plants.